Structural Design of Dry-Processed Lithium-Rich Mn-Based Materials with High Loading for Enhanced Energy Density - Yujie Ma; Haojin Guo; Tai Yang; Zhifeng Wang (Batteries)
With the growing demand for electric vehicles and consumer electronics, lithium-ion batteries with a high energy density are urgently needed. Lithium-rich manganese-based materials (LRMs) are known for their high theoretical specific capacity, rapid electron/ion transfer, and high output voltage. Constructing electrodes with a substantial amount of active materials is a viable method for enhancing the energy density of batteries. In this study, we prepare thick LRM electrodes through a dry process method of binder fibrillation. A point-to-line-to-surface three-dimensional conductive network is designed by carbon agents with various morphologies. This structural design improves conductivity and facilitates efficient ion and electron transport due to close particle contact and tight packing. A high-loading cathode (35 mg cm−2) is fabricated, achieving an impressive areal capacity of up to 7.9 mAh cm−2. Moreover, the pouch cell paired with a lithium metal anode exhibits a remarkable energy density of 949 Wh kg−1. Compared with the cathodes prepared by the wet process, the dry process optimizes the pathways for e−/Li+ transport, leading to reduced resistance, superior coulombic efficiency, retention over cycling, and minimized side reaction. Therefore, the novel structural adoption of the dry process represents a promising avenue for driving innovation and pushing the boundaries for enhanced energy density for batteries.